Pendefinisian Pasar Geografis dan Pasar Produk untuk Ritel Modern Jenis Supermarket di Indonesia Berdasarkan Perilaku Konsumen - Murman Budijanto (Performa: Media Ilmiah Teknik Industri, 2010)
Relevant markets definition is a crucial issue on anti-monopoly enforcement in many countries. The general approach of SSNIP (small but significant and non-transitory increase of price) is hardly applied to some cases, especially to a retail industry case. This descriptive research is trying to explore a possibility of using surveys to define a relevant market of supermarket services in Indonesia. Surveys were done to the consumers of supermarkets in Jakarta and five big cities outside Jakarta. Moreover it focuses on one of the biggest supermarket in Indonesia namely Carrefour and its competitors inside the geographical relevant markets. From these surveys, it is found that the relevant market of supermarket in Indonesia might include hypermarket and minimarket type of retails in Jakarta but only include hypermarket type of retails outside Jakarta. The difference is defined by significant number of the consumers who are choose minimarket as a substitute of supermarkets in Jakarta. This number is not quite significant in others five big cities outside Jakarta.